MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, PEMECAHAN MASALAH, DAN BERPIKIR KREATIF SISWA MENGGUNAKAN MODEL PATROLI PADA MATA PELAJARAN IPAS SEKOLAH DASAR - Zainal Ilmi, Muhammad; Refia Rafianti, Wahdah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this research is the low critical thinking, problem solving, and creative thinking skills of fifth-grade students at SDN Kuin Utara 5 Banjarmasin in the IPAS subject. The causes are learning that is still dominated by lecture methods, minimal discussion and collaborative activities, and suboptimal stimulation to encourage higher-order thinking skills. The proposed solution is the implementation of the PATROLI model. This research employed a qualitative approach with a Classroom Action Research (CAR) design. The research subjects were 13 fifth-grade students at SDN Kuin Utara 5 Banjarmasin. Data were collected through observation, tests, and documentation. The results showed that the PATROLI model effectively improved all aspects examined. Teacher activities increased from a score of 17 (85%) in meeting 1 to 20 (100%) in meeting 4. Student activities classically increased from 46% to 92%. Critical thinking skills increased from 46% to 85%, problem solving skills from 38% to 85%, and creative thinking skills from 38% to 85%. Cognitive learning outcomes increased from 46% to 85%, affective from 38% to 92%, and psychomotor from 38% to 92%. All indicators of success reached the target of ≥ 80% in the fourth meeting. Based on the research findings, it can be concluded that the PATROLI model is effective in improving teacher activities, student activities, critical thinking skills, problem solving skills, and creative thinking skills of students in the IPAS subject for grade V at SDN Kuin Utara 5 Banjarmasin.